2019
DOI: 10.1002/ece3.5415
|View full text |Cite
|
Sign up to set email alerts
|

Maternal genomic variability of the wild boar (Sus scrofa) reveals the uniqueness of East‐Caucasian and Central Italian populations

Abstract: The phylogeography of the European wild boar was mainly determined by postglacial recolonization patterns from Mediterranean refugia after the last ice age. Here we present the first analysis of SNP polymorphism within the complete mtDNA genome of West Russian (n = 8), European (n = 64), and North African (n = 5) wild boar. Our analyses provided evidence of unique lineages in the East‐Caucasian (Dagestan) region and in Central Italy. A phylogenetic analysis revealed that these lineages are basal to the other E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 54 publications
(113 reference statements)
1
24
0
Order By: Relevance
“…The mtDNA studies and localization of subfossil remains indicated that in Europe the species survived the Last Glacial Maximum (LGM) in southern refugia. The mtDNA lineages of wild boar inhabiting Italy, the Caucasus Mountains and the Near East are distinct from all other lineages occurring in western Eurasia 5 , 26 . Veličković et al 19 showed high frequencies of private microsatellite alleles in the populations inhabiting the three southern peninsulas (Iberian, Italian and Balkan), which confirmed the uniqueness of those populations.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The mtDNA studies and localization of subfossil remains indicated that in Europe the species survived the Last Glacial Maximum (LGM) in southern refugia. The mtDNA lineages of wild boar inhabiting Italy, the Caucasus Mountains and the Near East are distinct from all other lineages occurring in western Eurasia 5 , 26 . Veličković et al 19 showed high frequencies of private microsatellite alleles in the populations inhabiting the three southern peninsulas (Iberian, Italian and Balkan), which confirmed the uniqueness of those populations.…”
Section: Introductionmentioning
confidence: 86%
“…Almost all of them (except several individuals with Asiatic haplotypes, comp. 26 , 27 ) grouped in one mtDNA lineage called E1, which were further divided into clades E1-A and E1-C. The majority of individuals occurring in Central and Eastern Europe belonged to clade E1-C 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we report the same connections for the area situated north from the Caucasian mountain ridge. Khederzadeh et al [43] suggested the possibility of genetic connection of Dagestan wild boars to Italian rather than to Central of East European haplotypes. Our data indicate connection of Eastern Caucasus to NE clade.…”
Section: Plos Onementioning
confidence: 99%
“…Wu et al [16] suggested possible ways of expansion of pigs and wild boars within East-Asian regions but did not discuss how they could be related to western haplogroups. In the articles focusing on the genetic status of Near Eastern wild boars [20,43] animals from Turkey, Iran and Trans-Caucasian countries were described as belonging to European, Asian or Near Eastern haplogroups, but the history and relationships between these groups have not been discussed. Thus patterns of wild boar expansion in Asia remain unclear [12].…”
Section: Hypothesis About the Routes Of Wild Boar Dispersal In Asia Amentioning
confidence: 99%